Integrating metabolomics and transcriptomics to analyze differences in muscle mass and flavor formation in Gayal and yellow cattle - Han, Lin; Fu, Runqi; Fu, Binlong; Li, Qian; Yu, Ye; Gao, Huan; Zhang, Jiawei; Qi, Min; Jin, Chunjia; Mao, Shengyong; Leng, Jing (Frontiers in Veterinary Science, 2025)
Beef flavor is affected by muscle metabolites and their related regulatory genes, and the molecular regulatory mechanisms vary among different beef breeds. To provide some new ways to improve meat quality and cattle breed improvement, 24-month-old Gayal (n = 8) and yellow cattle (n = 8) were selected for comparison in this study. The result revealed that the longissimus dorsi muscle fiber diameter, protein content and a-value of Gayal were significantly higher than that of yellow cattle, but the fat content was lower than that of yellow cattle. Furthermore, Gayal meat contained notably higher levels of polyunsaturated fatty acids (PUFA) and n-3PUFA than that of yellow cattle, and also had better levels of flavor amino acids (FAAs) and sweet amino acids (SAAs), which contribute to the flavor of beef. Through comprehensive analysis of transcriptomics and metabolomics, we detected a total of 109 markedly different metabolites (DEMs) and 1,677 differentially expressed genes (DEGs) in the pectoral muscles of the two breeds. Further analysis indicated that amino acid and lipid metabolism might be the key factors contributing to the differences in meat quality and flavor between Gayal and yellow cattle, involving metabolites such as L-2-aminobutyric acid, L-glutamic acid, L-glutamine, L-serine, betaine, pantothenic acid, and taurine. Through correlation analysis, we identified genes highly associated with flavor amino acids (GSTM3, GSTT2), muscle development (FGF10, EIF4EBP1, PPP2R2C), and lipid metabolism (CYP4A22, ACOX3, PLIN1, ADH6, CNDP1, LPAR3, BRCA1, ADIPOQ, FABP3) related essential regulatory genes and constructed a gene-metabolite interaction network for meat quality and flavor formation in Gayal. In summary, it was shown that significant differences in muscle metabolites between Gayal and yellow cattle, especially in amino acid and lipid metabolism, may be the major reason for the differences in quality and flavor between the two types of beef. This study provides a theoretical basis for further exploring the molecular regulatory mechanisms of the differences in beef quality and flavor between Gayal and yellow cattle, and provides a reference for the development and genetic breeding of high-quality cattle breeds.